(untitled) (Prithvi Academic Journal, 2026)
Foreign labour migration has become one of the most crucial issues for economic prosperity in low-income societies worldwide. Migration-induced occupational changes are important determinants of socioeconomic progress among foreign labour migrants. This research investigates the determinants of occupational change among foreign labour migrants from the Gandarva, Majhi, and Kumal communities in Kaski, Nepal. The paper aims to ascertain the socio-economic determinants of occupational change and to compare occupational changes among migrant households. A mixed-method research design was employed, combining quantitative (n=121) and qualitative data (n=33) from migrants’ and returnees’ households. Due to the limited number of households among migrants and returnees in these communities, a census method, that is, including every household. Age, education, migration duration, remittance savings, and conditions in destination countries were employed as independent variables for occupational change. Multinomial logistic regression analysis revealed that age, migration duration, remittance savings, and the condition of the destination country had a significant influence on occupational change. Older migrants were more likely to move from unskilled to other occupations, while the length of migration and remittance savings had a positive impact on occupational mobility. Structural obstacles within destination countries discouraged career advancement. Elderly migrants were also more likely to return to unskilled work, while the duration of migration and remittance savings reduced the chances of downward mobility. The study recognises the interaction of demographic, economic, and contextual factors in shaping migrants’ occupational change. This indicates a need for policy interventions enabling financial literacy, skill development, and systematic remittance utilisation to optimise the economic benefits of migration.